2012
DOI: 10.1007/s12630-012-9684-x
|View full text |Cite
|
Sign up to set email alerts
|

L’esmolol versus l'association kétamine-rémifentanil pour une analgésie postopératoire précoce après cholécystectomie par laparoscopie: une étude randomisée contrôlée

Abstract: Intraoperative esmolol infusion reduces morphine requirements and provides more effective analgesia compared with a combination of remifentanil-ketamine given by infusion in patients undergoing LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 31 publications
(46 reference statements)
3
38
0
4
Order By: Relevance
“…In our view, this methodological distinction probably accounts for the different doses of esmolol and remifentanil in the Collard et al study compared with ours (1.3 vs 5.2 mgÁkg -1 ; and 7.6 vs 21 lgÁkg -1 , respectively). 1,5 We sincerely hope that this explanation resolves any confusion regarding the doses of esmolol administered in our study, as reflected in Table 1 of the article.…”
Section: Replymentioning
confidence: 67%
See 2 more Smart Citations
“…In our view, this methodological distinction probably accounts for the different doses of esmolol and remifentanil in the Collard et al study compared with ours (1.3 vs 5.2 mgÁkg -1 ; and 7.6 vs 21 lgÁkg -1 , respectively). 1,5 We sincerely hope that this explanation resolves any confusion regarding the doses of esmolol administered in our study, as reflected in Table 1 of the article.…”
Section: Replymentioning
confidence: 67%
“…1 We had originally planned to use a bolus dose of esmolol 0.5 mgÁkg -1 iv to be followed by a continuous infusion titrated according to patient requirements, at a rate from 5-15 lgÁkg -1 Ámin -1 , to maintain mean arterial pressure and heart rate within 20% of the patients' respective baseline values. However, soon after initiation of the study, we found that the dosing regimen initially planned made it impossible to achieve and maintain the desired hemodynamic goals.…”
Section: Replymentioning
confidence: 99%
See 1 more Smart Citation
“…Another randomized, placebocontrolled study stated the opioid-sparing effect of preemptive IV bolus ketamine (18). On the other hand, Lopez-Alvarez et al (19) indicated that morphine consumption and postoperative pain scores were higher in the group in which ketamine was administered. However, in this study, ketamine was only administered at induction; then, the patients received remifentanil infusion during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were placebo-controlled [5,[9][10][11][12], five were active-controlled [13][14][15][16][17], and one was placebo-and active-controlled [18]. Trial sizes ranged between 40 and 100 patients.…”
Section: Study Descriptionsmentioning
confidence: 99%